The Transmission of Seven Qur’anic Readings in Malang: Networks, Scholarship, and Pedagogical Dynamics - Lilik Badriyah; Miski, Miski (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2025)
This study examines the transmission of seven Qur’anic readings (qirā’āh sab‘ah) in Qur’anic boarding schools (pesantren) in Malang, East Java, a subject rarely addressed in Indonesian Qur’anic studies. It investigates how this tradition affirms the Qur’an’s authenticity while shaping networks of authority and pedagogy. Using a qualitative socio-historical approach that combines archival research and fieldwork, the study traces how knowledge of Qur’anic readings (qirā’āt) was transmitted, adapted, and legitimized. The findings reveal that continuity was secured through the agency of Kiai Mustain, whose transmission remained anchored in Kiai Arwani’s Fayḍ al-Barakāt. Although later generations adjusted teaching methods to contemporary contexts, their authority was sustained by genealogical fidelity, interpersonal bonds, and institutional ties. The study argues that the network of Qur’anic readings in Malang developed into an elite form of scholarship, simultaneously reinforcing conventional authority structures and adapting to changing educational and social dynamics. These findings contribute to broader discussions on Qur’anic transmission, religious authority, and pedagogical adaptation in Southeast Asian Islam.